IMPROVING STUDENTS’ ABILITY IN TRANSLATING THROUGH ANALYZING ENGLISH WORD EQUIVALENTS INTO INDONESIAN - . Sholihin (Magister Scientiae, 2015)
The objective of the research is “ To know the improvement of the students’ ability in translating through analyzing English word equivalent into Indonesian. This research used A Classroom Action Research (CAR). It had conducted two cycles; each cycle consisted of four meetings. A number of subjects of the research were 28 students. The researcher took real data from the school to know the students’ translating text achievement. The instruments of this research were translating test and observation sheet in cycle I and in cycle II. The research findings indicated that the through analyzing on English Words equivalents into Indonesian increased studensts’ translating text ability. It was indicated that there was an increased of the students’ translating text ability achievement from cycle I to cycle II. The students’ test of translating text ability achievement was after giving action by using the analyzing on English Words equivalents into Indonesian indicated that there was a significant increase from cycle I and from that to cycle II. The students’ translating text achievement in cycle I was 61.20 and in cycle II became 73.78 and it is classified as good. While the standard target achievement 70% one which was categorized good. From these findings, there was a significant increase of the students’ translating ability achievement through the analyzing on English Words equivalents into Indonesian. Key Word: analyzing english word equivalent into indonesian, translating.